The German Aesthetic Tradition - Hammermeister, Kai (Cambridge Cambridge University Press, 2002)
This book, first published in 2002, is a systematic critical overview of German aesthetics from 1750 to the present. It begins with the work of Baumgarten and covers all the major writers on German aesthetics that follow, including Kant, Schiller, Schelling, Hegel, Nietzsche, Heidegger, Gadamer and Adorno. The book offers a clear and non-technical exposition of ideas, placing these in a wider philosophical context where necessary. Such is the importance of German aesthetics that the market for this book will extend far beyond the domain of philosophy to such fields as literary studies, fine art and music.
Keywords: Baumgarten, Alexander Gottlieb -- 1714-1762; Kant, Immanuel -- 1724-1804; Schiller, Friedrich -- 1759-1805; Schelling, Friedrich Wilhelm Joseph von -- 1775-1854; Hegel, Georg Wilhelm Friedrich -- 1770-1831; Nietzsche, Friedrich Wilhelm -- 1844-1900; Heidegger, Martin -- 1889-1976; Gadamer, Hans-Georg -- 1900-2002; Adorno, Theodor W. -- 1903-1969; 18th Century (1701-1800); 19th Century (1801-1900); 20th Century (1901-2000); Esthetics; Germany